Quality management service at the University of Malaya Library. - Kaur, K.; Pauziaah, M.; George, S. (Emerald Group Publishing Limited, 2006)
Purpose – This paper aims to describe the steps in attaining the ISO 9001:2000 quality management system certification at the University of Malaya Library.